Pengaruh Kompetensi Dan Karakteristik Wirausaha Terhadap Perkembangan Usaha Mikrpo Kecil Dan Menengah (UMKM) (Studi Kasus Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Koto Baru) - Cici Permata Sari; Nurhayati Nurhayati; Ida Nirwana (Journal of Creative Student Research, 2023)
Based on the observations of Micro, Small and Medium Enterprises (UMKM) actors in Koto Baru, Solok Regency, in general these MSMEs are not optimistic in running their business, it can be seen from the many business owners who are not confident to compete, most of them think they are not able to compete with other UMKM who have run their business first. business, when in fact the products they have can compete and can even be better if they can be managed properly and lack of knowledge and skills about business management and the use of technology, including licensing issues, administrative problems and other simple bookkeeping. The aim is to find out how the competencies and characteristics of Micro, Small and Medium Enterprises (UMKM) in Koto Baru are.This research was carried out at the new Koto UMKM with the address at Koto Baru, Kubung District, Solok Regency, West Sumatra. This type of research uses a descriptive quantitative approach. Sources of data used in this study is primary through the distribution of questionnaires regarding the competence and characteristics of entrepreneurship on business development. The sampling technique was done by purposive sampling, as many as 70 people.The results show that partially entrepreneurial competence has a positive effect on business development, the t-count value is greater than t-table, namely 5.041> 1.9954, and the significant value is 0.000 <0.05 and entrepreneurial characteristics have a positive effect on business development. t table is 4.092 > 1.9954 and the value is significant 0.000 <0.05. Based on the F test, the Fcount value is 14,642 and the Ftable value is 3,13. This states that simultaneously or simultaneously competence and entrepreneurial characteristics have a positive effect on the development of the Koto Baru UMKM business.